Ammonium-Nitrogen Recovery from Wastewater by Struvite Crystallization Technology. Issue 4 (1st October 2016) - Darwish, Mohamad; Aris, Azmi; Puteh, Mohd Hafiz; Abideen, Muzaffar Zainal; Othman, Mohd Nor
Abstract : Struvite crystallization is one of the sustainable approaches for recovering ammonium nitrogen (NH4 -N) from wastewater in the form of a valuable material, in parallel with improving wastewater treatment efficiency. Focusing on NH4 -N recovery, this review discusses the factors influencing struvite crystallization including the effect of foreign elements. It is shown that more than 95% of NH4 -N could be recovered in the form of struvite, a magnesium-ammonium phosphate (MAP) salt, from some kinds of wastewater. This review emphasizes the role of utilizing alternative sources of Mg and P in improving the process sustainability. Additionally, it also explains how the MAP precipitation process could result with significant reduction of other pollutants contributing to total organic carbon, of color and turbidity, which support MAP integration with other treatment methods. The main options of lowering MAP recovery cost are presented; it was shown that applying low-cost materials of both Mg and P could save more than 65% of the process's cost. Finally, the future research directions to improve NH4 -N recovery are pointed out.